Virtual Catharsis : Decoding Empathy in VR Refugee Narratives in the UNVR Films - Elmeligi, Wessam; Khattab, Mona (Palgrave Macmillan, 2024)
Among recent attempts employing newer methods of communication with more user engagement is the use of Virtual Reality (VR) to produce immersive experiences centred on the plight of refugees. With the features of the VR environment designed to induce more immediacy and participation, VR videos are produced targeting audience empathy through virtual proximity to the dire living conditions of refugees. This chapter poses the following questions: How far have psychological and literary elements of catharsis informed the use of VR technology and to what degree has VR redefined catharsis as a mode of empathy delivered via an audio-visual and spatial immersive media experience? Adopting immersive media narrative analysis, this study examines films produced by the United Nations in a project known as UNVR to present various humanitarian causes. Focusing on two UNVR films, Clouds over Sidra (2015) and Life in the Time of Refuge (2016), the chapter examines the potential for empathy through the intersectionality of VR technology and narrative in light of the concept of virtual catharsis.
Keywords: immersive media; empathy machine; refugee crisis; virtual reality